AN EQUIVALENCE STUDY OF POLISH AND JAPANESE TERMS IN CIVIL LAW - HORIE, Yuki (Comparative Legilinguistics, 2014)
Comparing the terminology in Polish and Japanese civil law, it can be divided into the following four groups; the first group, in which there are equivalents in both languages with the same meaning; the second group, in which the equivalents exist, but in one language the semantic field is wider; the third group, in which the equivalents exist, but their semantic fields to some extent are not identical; and the last one, in which there are no equivalents. In this article I would like to analyze the Polish-Japanese legal terminology in accordance with that division into four groups.